Ultrasound-Assisted Food Processing: A Mini Review of Mechanisms, Applications, and Challenges - Alshehhi Mahra; Wu Guowei; Kangsadan Tawiwan; Chew Kit Wayne; Show Pau Loke (E3S Web of Conferences, 2023)
Ultrasound technology in food processing holds promise in terms of energy efficiency, environmental impact, and sustainability compared to traditional processing methods. These conventional heat-based techniques, such as salting, smoking, and frying, are energy-intensive and time-consuming. Therefore, ultrasound as a promising technology has attracted the interest of scientists and stakeholders in the food processing field. This alternative solution utilizes ultrasound and can achieve similar results with reduced energy input. This not only reduces energy consumption but also contributes to reducing carbon footprint and greenhouse gas emissions. In addition, ultrasound processing technology enhances food safety and quality by inhibiting microbial growth and killing pathogens, leading to longer shelf life and reduced food waste. However, there are also present some limitations of ultrasound in food processing through dense and complex food matrices like protein. Current research and development efforts are expected to address these challenges and expand applications in food processing. Overall, ultrasonic technology could transform the sustainability of food processing in the future.